2017
DOI: 10.24908/pceea.v0i0.6519
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Design Engineers: Attitudes, Opinions and Potentially Influential Factors

Abstract: -The results for the Engineering students are emphasized, but they are also compared with students and faculty from other Colleges. Closed questions were analyzed using inferential statistical tests (distributions, means, standard deviations, t-tests, ANOVA, Cronbach's alpha), while the open-ended responses are compared more qualitatively when they cannot be quantified easily.The survey went through ethics approval and was distributed in the latter half of the Fall 2015 term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The methods for data gathering using the 2015 survey are described in detail in [2]. In short, an online pilot survey was distributed to students and faculty from a variety of Colleges, including Engineering, at the University of Saskatchewan during the Fall 2015 term.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods for data gathering using the 2015 survey are described in detail in [2]. In short, an online pilot survey was distributed to students and faculty from a variety of Colleges, including Engineering, at the University of Saskatchewan during the Fall 2015 term.…”
Section: Methodsmentioning
confidence: 99%
“…These questions help us to examine effects that originate from family backgrounds and personality shaping factors, and to identify other variables explaining attitudes and values about creativity over and above these other factors. The highlights of the results for each of these demographic questions were shared in [2].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Creativity is also important to engineers: Neufeld et al [14] found that engineers and engineering students value creativity, that creativity is generally a positive behavior, and 92% of respondents from the College of Engineering felt they were creative at least some of the time.…”
Section: Creativity In Engineeringmentioning
confidence: 99%